2017
DOI: 10.1016/j.omtm.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Enzyme Replacement to the Brain of a Late Infantile Neuronal Ceroid Lipofuscinosis Mouse Has Differential Effects on Phenotypes of Disease

Abstract: Late infantile neuronal ceroid lipofuscinosis (LINCL) is a fatal inherited neurodegenerative disease caused by loss of lysosomal protease tripeptidyl peptidase 1 (TPP1). We have investigated the effects of chronic intrathecal (IT) administration using enzyme replacement therapy (ERT) to the brain of an LINCL mouse model, in which locomotor function declines dramatically prior to early death. Median lifespan was significantly extended from 126 days to >259 days when chronic IT treatment was initiated before the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…It is worth noting that in a recent study from our laboratory, 19 fluorescent rhTPP1 was delivered to the brain via the cerebrospinal fluid (CSF) using an intrathecal injection. Here, overall distribution of rhTPP1 was quite uneven, with the most efficient delivery to ventral surfaces of the brain and very poor or undetectable delivery to dorsal and deep brain regions, such as the hippocampus.…”
Section: Brain Distribution Of Rhtpp1 Delivered By K16apoe-mediated Umentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that in a recent study from our laboratory, 19 fluorescent rhTPP1 was delivered to the brain via the cerebrospinal fluid (CSF) using an intrathecal injection. Here, overall distribution of rhTPP1 was quite uneven, with the most efficient delivery to ventral surfaces of the brain and very poor or undetectable delivery to dorsal and deep brain regions, such as the hippocampus.…”
Section: Brain Distribution Of Rhtpp1 Delivered By K16apoe-mediated Umentioning
confidence: 99%
“…Sections were prepared for whole-slide imaging as described. 19 Biotin staining was conducted as described. 34…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrathecal injection of TPP1 slows down CLN2 disease in mice and humans. Flupirtine and aromatic carbamate derivatives antiapoptotic properties provide the basis for use as potential therapies in NCL disease.…”
Section: Introductionmentioning
confidence: 99%
“…This could indicate either triggering of pathophysiological pathways that cannot be reversed by restoration of TPP1, or accumulated storage material in a subset of cell types that becomes refractory to clearance. We have also conducted enzyme replacement therapy (ERT) in the LINCL mouse [ 10 , 11 ] and again found that earlier treatment was again more effective. However, an unexpected finding was that a subset of highly-symptomatic animals responded well to treatment, with significantly increased lifespan [ 10 ].…”
Section: Introductionmentioning
confidence: 99%